Ukraine : Technical Assistance Report-Distributed Profit Tax; Voluntary Disclosure of Assets; and BEPs Implementation. (IMF Staff Country Reports; Country Report, 2019)
This Technical Assistance report focuses on Ukraine's distributed profit tax, voluntary disclosure of assets, and Base Erosion and Profit Shifting Work Program implementation. The recommendations largely favor simplifying rules, improving the definition of basic concepts, eliminating potential loopholes, and adhering more closely to international standards in some cases. Thus, for the sake of simplification, the report recommends that Controlled Foreign Corporation rules should apply to the 'first onshore' person rather than having to trace them back to the ultimate beneficial owner in Ukraine. Also, it recommends that the proposed interest deduction limitation should eliminate the carry-forward currently permitted, limit deductions to net interest expense and exempt the financial sector from this limitation. Some key definitions can be improved too. The report suggests that if there is an urgent need to promote private investments, the accelerated depreciation tool should be applied for plant and machinery and structures housing them for say another five years.